Gaya Kepemimpinan Guru dalam Mengajar Generasi Z Mata Pelajaran Bahasa Inggris di Sekolah Islami dan Nonislami di Provinsi Jambi - Armida, Armida; Pratama, Aryawira; Firmansyah, Dedi Wahyu (Paedagogie, 2026)
Teacher leadership style plays a crucial role in determining the success of English language learning, particularly in teaching Generation Z students, who are characterized by their digital, critical, and dynamic nature. However, the implementation of teacher leadership styles often faces different challenges in school contexts with diverse religious backgrounds. This study aims to identify dominant and effective teacher leadership styles in English language learning and analyze the challenges and mitigation strategies implemented by teachers in Islamic and non-Islamic schools in Jambi Province. The main problem of this research lies in the lack of in-depth exploration of teacher leadership practices in addressing the learning needs of Generation Z in the context of multicultural and multireligious education. This research uses a qualitative approach with a case study design. Data were collected through semi-structured interviews and classroom observations, then analyzed using thematic analysis. The results show that transformational, instructional, and ethical leadership styles are the most dominant and effective styles applied by teachers. These leadership styles have a positive impact on the motivation, engagement, and learning climate of Generation Z students. In conclusion, adaptive and value-based teacher leadership is the key to successful English language learning in schools with diverse religious backgrounds.